The Meaning of “Career Success” for the Alpha Generation: A Narrative Study of Young People Entering the Workforce in the Hybrid Era - Kurniawan, Agung Widhi (PT Maju Malaqbi Makkarana, 2025)
This qualitative study explores how Generation Alpha (born 2010–2024) defines career success as they enter the hybrid workforce through part-time or gig roles. Using life-history interviews with 15 early Gen Alpha workers (aged 14–18), the research reveals that their perceptions of success prioritize flexibility, digital literacy, and purpose-driven work over traditional metrics like salary or job titles. Thematic analysis identified three key themes: (1) success as autonomy in work-life boundaries, (2) success tied to mastery of digital tools, and (3) alignment between personal values and employer ethics. These findings challenge conventional HR frameworks, suggesting that organizations must adapt career development programs to accommodate Gen Alpha’s distinct expectations. The study contributes to generational theory and hybrid work literature by highlighting the evolving intersection of technology, identity, and labor.